Higienização das mãos: conhecimento e adesão de profissionais da saúde em unidade de pronto-socorro - Piasentin, Caroline Zottele (2016)
Hand hygiene (HH) is not only an effective prime precaution in reducing adverse events but also a major challenge in different fields of care practice and scientific research. The present study aimed at assessing the knowledge and adoption of health professional regarding hand hygiene in emergency room unit. This research comprehends a prospective longitudinal study with quantitative approach. The study was developed at the emergency room of the University Hospital of Santa Maria (HUSM), with 69 health professionals (residentes, nurses, nursing technicians and physiotherapists) who maintained direct contact with a clinically stable patient. The data collection was made between March and July of 2015, using instruments validated by the World Health Organization (WHO), in two stages. On the first stage, the non-participant direct observation tehcnique was applied, with an Observation form being filled in by the researcher. During the observation the five moments recommended for HH were accompanied, taking into account the concepts of Opportunity, Indication and Action. Each professional was observed in three different moments, with an average interval of 15 days (SD=9) between sessions. The time interval between the first and the last observations consisted of an average 28 days difference (SD=9). On the second stage, the subjects answered the Test of knowledge regarding hand hygiene for health professionals questionnaire, composed of right and wrong questions. The data organization was made using the Epi-info® software, version 6.4, with double independent typing. After verifying the errors and inconsistancies, the data analysis was made using the PASW Statistics® (Predictive Analytics Software, by SPSS Inc., Chicago, USA) 18.0 software, by means of descriptive analytical statistics. 59 out of the 69 health professional were accompanied during three observation sessions. 53 out of the 59 answered the questionnaire. In 111 days of observation, 166 sessions were made, with an average 11 minutes duration each (SD=50s). On such sessions 166 oportunities for HH were observed, however HH took place in 90. The global rate of adoption was 54,2%; 50,8% during the first observation and 59,6% during the last. Nurses and physiotherapists were the professional with the highest rates of adoption (66,6%; p<0,05). When comparing the rate of adoption between professional categories, nurses were found to have a larger adoption of HH than nursing technicians (OR: 2,83; IC: 95% [1,08 7,4]). The other categories presented no statistic difference. Regarding the knowledge questionnaire, the largest percentage of correct answers, over 90%, referred to route of transmission, technique, products and transmission to the health professional. Conclusion: The low adoption and restricted knowledge regarding the benefits of using alcohol for HH lead to the necessity of additional investment in capacitations for the health professional about safe practices relating to HH, aiming to increase the safety culture for the patient in emergency room.